Development of a Platform Supply Vessel: Design, Resistance Assessment, and Prototype Fabrication for Offshore Operations in Natuna, Indonesia - Fathin Muhammad Mahdhudhu; Fakhri Akbar Ayub; Muhammad Akmal Apriansyah Efendy; Muhammad Ivan Kurniawan; Choirul Anam; Fathan Mubina Denu; Nabillah Jasmine Anugrahputri (Fakultas Teknik Universitas Pancasila, 2026)
Maritime transportation serves as a vital component of inter-island connectivity in Indonesia, particularly in supporting offshore oil and gas exploration activities. This study focuses on addressing the rarity of Platform Supply Vessel in the Natuna Islands, which are needed to support offshore operations to optimize the exploration of Natuna's abundant natural resources. The design process begins with the determination of the vessel’s principal dimensions, derived from benchmark vessel data and dimensional ratio analysis. The hull form is subsequently developed into a 3D model to produce a lines plan. Resistance analysis is conducted based on the Holtrop method, encompassing components such as frictional resistance, wave-making resistance, transom drag, and air resistance. A scaled physical model is also constructed using a non-molded hull fabrication technique to validate the design. The findings indicate that the proposed hull design satisfies the specified performance criteria and demonstrates favorable resistance characteristics. This research answers the rarity of studies on Platform Supply Vessel specifically for Natuna by contributing a comprehensive study focusing on design, fabrication, and cost analysis.